2020
DOI: 10.1002/bmc.4739
|View full text |Cite
|
Sign up to set email alerts
|

Serum metabolomics study of patients with allergic rhinitis

Abstract: Allergic rhinitis (AR) negatively affects the healthy lives of many individuals. Most previous studies on AR focused on the expression of cytokines, with only a few analyzing cytokine expression from a metabolomics viewpoint. Therefore, it is worthwhile to study AR at the metabolic level. Consequently, we aimed to identify differential serum biomarkers by metabolomics. In this study, the orthogonal partial least squares discriminant analysis (OPLS‐DA) model was applied to characterize the differences in serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…Metabolites have also been proposed as biomarkers for AR. A very recent study of serum metabolomics has demonstrated that at least nine metabolites (13(S)‐HPODE, bilirubin, leukotriene D4, hypoxanthine, L‐stercobilinogen, N‐succinyl‐L‐diaminopimelic acid, chlorophyll b, 15‐hydroxyeicosatetraenoic acid and urate) were significantly altered in the serum of AR patients and therefore may provide a better understanding of the metabolic pathways involved in the etiology of AR 94 . Additionally, a decreased serum lactoferrin level has been reported to be associated with the phenotype of Dermatophagoides pteronyssinus (Der p 1)‐sensitive AR and, in combination with serum Der p 1‐specific IgE levels, may serve as a serologic biomarker for early detection of AR 95 …”
Section: Biomarkers In Diagnosis Of Allergic Rhinitismentioning
confidence: 99%
“…Metabolites have also been proposed as biomarkers for AR. A very recent study of serum metabolomics has demonstrated that at least nine metabolites (13(S)‐HPODE, bilirubin, leukotriene D4, hypoxanthine, L‐stercobilinogen, N‐succinyl‐L‐diaminopimelic acid, chlorophyll b, 15‐hydroxyeicosatetraenoic acid and urate) were significantly altered in the serum of AR patients and therefore may provide a better understanding of the metabolic pathways involved in the etiology of AR 94 . Additionally, a decreased serum lactoferrin level has been reported to be associated with the phenotype of Dermatophagoides pteronyssinus (Der p 1)‐sensitive AR and, in combination with serum Der p 1‐specific IgE levels, may serve as a serologic biomarker for early detection of AR 95 …”
Section: Biomarkers In Diagnosis Of Allergic Rhinitismentioning
confidence: 99%
“…Adamko et al provided conceptual evidence that metabolomic analysis of excreted urine metabolites could distinguish severity in patients with AR (52). A recent serum metabolomics study showed that at least nine metabolites (13(S)-HPODE, bilirubin, leukotriene D4, hypoxanthine, L-steroidal bilirubin, N-succinyl-L-diaminoheptanedioic acid, chlorophyllb, 15hydroxyeicosatetraenoic acid, and uric acid) were significantly altered in the serum of patients with AR (53). Another study identified serum biomarkers that can reliably and correctly predict the efficacy of sublingual immunotherapy in patients with AR (54).…”
Section: Discussionmentioning
confidence: 99%
“…They were all treated with SCIT for 1 year. In addition to the detailed inclusion criteria in the method above, other covariates, such as genders and fasting or not, were not taken into account, since the current study on human does not indicate the impact of other covariates on the results (Adamko et al, 2018;Ma et al, 2019). Through metabolomics detection and analysis of serum from these patients before and after treatment, we studied the difference of metabolic levels in Artemisia sieversiana pollen allergic rhinitis patients before and after 1-year of SCIT treatment by metabonomic method, and combined with the physiological and biochemical significance of different metabolites and related metabolic pathways, we made some positive discoveries.…”
Section: Discussionmentioning
confidence: 99%